Nonlinear Radial Consolidation Analysis of Soft Soil with Vertical Drains under Cyclic Loadings - Pyol Kim; Hyong-Sik Kim; Yong-Gun Kim; Chung-Hyok Paek; Song-Nam Oh; Sung-Ryol So; Chang-Son Ok (Shock and Vibration)
This paper presents analytical solutions for nonlinear radial consolidation of soft soil with vertical drains under various cyclic loadings. By considering the nonlinear variations of compressibility and permeability expressed by the logarithm relations (e−log σ′ and e−log kh), the governing equation for nonlinear radial consolidation of the soil under equal strain and time-dependent loading is established. The analytical solutions are derived for nonlinear radial consolidation under haversine cyclic loading, trapezoidal cyclic loading, rectangular cyclic loading, and triangular cyclic loading. The presented solution is verified through the degeneration into the existing solutions for nonlinear radial consolidation under constant and ramp loadings, which shows the solution proposed in this paper is more general for nonlinear radial consolidation under time-dependent loading. The nonlinear radial consolidation behavior of the soil with vertical drains subjected to various cyclic loadings is investigated using the solutions developed. The proposed solutions can be effectively utilized in the analysis of nonlinear radial consolidation under various cyclic loadings.